2020
DOI: 10.1101/2020.01.13.904227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germination response of invasive plants to soil burial depth and litter accumulation is species specific

Abstract: AbstractQuestionsPlant invasions are considered among the biggest threats to biodiversity worldwide. In a full-factorial greenhouse experiment we analysed the effect of soil burial depth and litter cover on the germination of invasive plants. We hypothesised that (i) burial depth and litter cover affect the germination of the studied species, (ii) the effects of burial and litter cover interact with each other, and (iii) the effects are specie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Some seedlings emerged in pots even with the highest litter and soil cover levels. These results were in line with most findings of Sonkoly et al (2020) where the germination of 11 invasive species were tested. Mirroring also the results of the latter study, the small-seeded S. cryptandrus had the highest seed germination rates with 0.5 cm soil burial depth with no litter cover.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some seedlings emerged in pots even with the highest litter and soil cover levels. These results were in line with most findings of Sonkoly et al (2020) where the germination of 11 invasive species were tested. Mirroring also the results of the latter study, the small-seeded S. cryptandrus had the highest seed germination rates with 0.5 cm soil burial depth with no litter cover.…”
Section: Discussionsupporting
confidence: 89%
“…Species-specific information on the aspects of the seed bank formation and early establishment patterns of an invasive species is crucial for developing strategies for its suppression and for the prevention of its further spread (Gioria et al 2012, Sonkoly et al 2020). We found that increasing cover of S. cryptandrus decreases the species richness and abundance of subordinate species both in the vegetation and seed banks.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances such as grazing, mowing or fire may result in the elimination of litter and the perturbation of the soil surface, which may facilitate the germination of invasive plants. Sonkoly et al (2020, this issue) studied how soil burial depth and litter cover affect the germination of invasive species and whether differences between species’ response can be explained by seed size. Their results showed that there are considerable differences in species’ responses to being buried by soil or litter, highlighting the need to study further how disturbance events that perturb soil and litter layers shape species’ establishment and vegetation dynamics.…”
Section: Germination and Recruitmentmentioning
confidence: 99%
“…Seedling number was the number of germinated seedlings per pot. Biomass referred to the dry biomass of the germinated seedlings per pot and was used as a proxy of seedling fitness (Sonkoly et al 2020). Mean germination time (days) was calculated for the seedlings of each pot.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Previous studies have shown the potential of bleaching for breaking the dormancy of seeds of grass (Hsiao 1979) and legume species (Okonkwo and Nwoke 1975). Besides studying seedling numbers, we also used seedling biomass as a proxy for seedling fitness (Sonkoly et al 2020). We used three variables, i.e.…”
Section: Introductionmentioning
confidence: 99%